Sustainability from household and infrastructure innovations - Allen, Peter M.; Butans, Eugene; Robinson, Marguerite; Varga, Liz (Springer, 2021)
In this paper, we look at the impact of different possible changes and innovations in the national/regional infrastructure and of individual households on the reduction of their material ‘footprint’ and carbon emissions. We have developed an ‘agent-based model’ (ABM) that explores the impact of possible changes in regional infrastructure and in ‘household agent’ behaviour and lifestyles. We study households of the UK, Germany, Spain and Finland, and calculate the overall effects of the diffusion of such changes and innovations. The ‘lifestyle’ of households is divided into four different ‘Domains’—Living, Food, Mobility and Energy. For each change, the model shows the linked effects of adoption, and total household input requirements (materials, energy etc.), household and food wastes and CO2 emissions. This informs policy concerning which modifications will be most effective. We can also estimate approximately how much ‘clean’ electricity will be needed in each country for household needs and their electric vehicles
Keywords: Clean electricity; Material footprints; Household system; ABM model; Household changes and innovations; Sustainability